Perubahan Lingkungan Permukiman Mikro Daerah Perkotaan berbasis Konsep Tri Hita Karana di Kabupaten Buleleng Bali - Wesnawa, I Gede Astra (Forum Geografi, 2010)
This research was carried out in area of urban of Buleleng regency. The aim of the research: (a) to identify form of changes of urban settlement environment on the basis of THK, (b) to study change factor of urban micro settlement environment on the basis of THK in Buleleng regency, (c) study process of change of urban micro settlement environment, what factors had an effect on to the change, and (d) study fade in what impact of existence of change of urban micro settlement environment on the basis of THK. This research duration during 2 year. First year focus on identifying form of changes and study cause of change of urban micro settlement environment. The method research by using survey design. Sampling is sampling subject was chosen with technique in stratified random sampling. Analysis was analytical technique qualitative supported with quantitative data to change of urban micro settlement environment which based on at concept THK. Research results show that: Identify form of change of applying of concepts THK in urban micro settlement. The cause of change of urban micro settlement environment on the basis of THK. Research result in the forms of change of urban micro settlement environment and cause of change of environment, relate to development of urban micro settlement basis of Tri Hita Karana in urban of Bali, as a form of innovation and enable of urban area as strategic way out and anticipation for sub-province local government in overcoming various problems of development of the areas for the agenda of areas autonomies, specially concerning of settlement environment.